2014
DOI: 10.3389/fpls.2014.00432
|View full text |Cite
|
Sign up to set email alerts
|

WHIRLY1 is a major organizer of chloroplast nucleoids

Abstract: WHIRLY1 is an abundant protein of chloroplast nucleoids, which has also been named pTAC-1 with regard to its detection in the proteome of transcriptionally active chromosomes (TAC). In barley primary foliage leaves, expression of the WHIRLY1 gene is highest at the base whereas protein accumulation is highest in the middle of the leaf where young developing chloroplasts are found. In order to elucidate the function of WHIRLY1 in chloroplast nucleoids, transgenic barley plants with an RNAi-mediated knock-down of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
94
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 50 publications
(103 citation statements)
references
References 55 publications
9
94
0
Order By: Relevance
“…The transcript profile analysis of the WHIRLYdeficient leaves showed that genes encoding discrete subsets of photosynthetic proteins were markedly changed relative to the wild type. These findings are consistent with the observation that barley leaves seem to be less able to regulate cpDNA copy number in the absence of WHIRLY1 (Krupinska et al, 2014b). Transcripts encoding photosynthetic proteins, including the thylakoid NADH dehydrogenase and cytochrome b/f complexes, and chloroplast ribosomes were more abundant in the WHIRLY-deficient leaves than the wild type.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The transcript profile analysis of the WHIRLYdeficient leaves showed that genes encoding discrete subsets of photosynthetic proteins were markedly changed relative to the wild type. These findings are consistent with the observation that barley leaves seem to be less able to regulate cpDNA copy number in the absence of WHIRLY1 (Krupinska et al, 2014b). Transcripts encoding photosynthetic proteins, including the thylakoid NADH dehydrogenase and cytochrome b/f complexes, and chloroplast ribosomes were more abundant in the WHIRLY-deficient leaves than the wild type.…”
Section: Discussionsupporting
confidence: 90%
“…This transcript is identical to the barley organelle DNA polymerase described recently (Krupinska et al, 2014a(Krupinska et al, , 2014b and homologous to the AtPol1B (At3g20540) sequence. Similarly, a microtubule end binding protein 1A (MLOC 52339.1) and a transcript encoding a protein containing a B3 DNA binding domain (AK251585.1) that is found exclusively in transcription factors were significantly more abundant in W1-7 leaves relative to the wild type ( Fig.…”
Section: The Transcript Profile Is Modified In Whirly1-deficient Leavessupporting
confidence: 58%
See 3 more Smart Citations